PPM USAHA MIKRO MAKANAN WONTON KOTA BARU DRIYOREJO GRESIK - Permadi, Edo Galih; Waras, Waras; Muzakki, Muzakki (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Partners are Wonton food UMKM entrepreneurs who have problems in production, marketing, and finance. Problems in production include inadequate production equipment such as small and easily problematic meat grinders, limited coolers for storing food, and insufficient product variety because there are only 2 flavors. Problems in marketing include the lack of marketing tools such as not having a banner showing the product and brand, not having a brand logo as a business identity, and marketing that is only limited to neighbors and acquaintances. Problems in finance include partners making financial reports manually and simply. The objectives of the PKM activities carried out in general are: 1) increasing the number of partner production; 2) increasing partner product variants; 3) increasing partner product sales; 4) improving partner business financial management. The method of implementing PKM is through grants of meat grinders, coolers, and banners, as well as training. The results of community service show the enthusiasm of partners to undergo the program and improve their business performance. Through the active participation of partners, partner's business problems can be overcome. The impact of this PKM are 1) increasing partner production, 2) increasing partner skills in doing business, 3) increasing partner business performance. Keywords: Wonton, UMKM, Food, PKM